AB0447 Patterns of Biologic Discontinuations within the Corrona Registry: Certain Study. (9th June 2015) - Pappas, D.A.; John, A.; Curtis, J.R.; Etzel, C.J.; Karki, C.; Ssemakula, J.; Kremer, J.M.; Shewade, A.; Greenberg, J.D.
Abstract : Background: There are limited data describing patterns of discontinuations of biologic therapy for rheumatoid arthritis (RA) in real-world settings. Such information could help clinicians understand real-life treatment patterns and serve as a marker of effectiveness to help inform decisions. Objectives: To describe the patterns and reasons for discontinuation of biologics within 1 year after initiation of treatment in the Corrona C omparative E ffectiveness R egistry to study T herapies for A rthritis and I nflammatory Co n ditions (CERTAIN) study. Methods: CERTAIN is a prospective, nonrandomized, comparative effectiveness cohort study nested within the US Corrona registry and included adult patients with RA who have at least moderate disease activity (Clinical Disease Activity Index >10) and are starting or switching biologics. 1 This descriptive study included all patients who initiated a biologic in CERTAIN and discontinued the biologic or switched to a different biologic before their 12-month follow-up visit. Reasons for discontinuation were evaluated based on physician's report and categorized as efficacy reasons, safety reasons, both and other reasons unrelated to safety or efficacy. Results: A total of 2361 patients enrolled in CERTAIN contributed 2809 all-biologic initiations to this analysis, which included 1670 anti–tumor necrosis factor agents (aTNFs) and 1139 non-aTNFs. At the time of the analysis, data were available for 1174 biologic initiations from patients who completed CERTAIN, with 344 initiations still in follow up. Baseline characteristics at the time of biologic initiation were as follows: median age, 57 years; female, 79%; median RA duration, 5 years; and rheumatoid factor (RF) and/or anti-cyclic citrullinated peptide (ACCP) antibody seropositivity, 68%. After excluding those initiations still in follow up, 909 of 2465 initiations (37%) resulted in a discontinuation within 12 months, with reasons for discontinuation available for 635 patients (70%; Table ). A higher proportion of biologics were discontinued by the 3-month follow-up visit due to safety reasons, while a higher proportion of initiations were discontinued after the 3-month follow-up visit due to efficacy reasons ( P <0.001). Characteristics of patients who discontinued biologic treatment for any reason were as follows: median age, 56 years; female, 83%; median RA duration, 5 years; and RF and/or ACCP seropositivity, 67%. The median (IQR) duration on biologic at the time of discontinuation/switch was 4.2 (2.5-6.3) months. Conclusions: This analysis evaluated reasons for discontinuation of biologics in a US real-world setting. Safety reasons are more commonly responsible for drug discontinuation early after initiation of therapy and become less common later in therapy. An opposite pattern was observed for discontinuations due to decreased efficacy. There were no significant differences in reasons for discontinuation by prior biologic use or for treatment as monotherapy vs combination therapy. References: Pappas DA, et al. BMC Musculoskeletal Disord. 2014;15:113. Acknowledgements: The Corrona CERTAIN study is sponsored by Corrona, LLC, with support from Genentech, Eli Lilly, Momenta Pharmaceuticals and Pfizer. Disclosure of Interest: D. Pappas Employee of: Corrona, LLC, Paid instructor for: Novartis, A. John Employee of: Genentech, Inc, J. Curtis Grant/research support from: AbbVie, Amgen, BMS, Corrona, Crescendo, Janssen, Pfizer, Roche/Genentech and UCB, Consultant for: AbbVie, Amgen, BMS, Corrona, Crescendo, Janssen, Pfizer, Roche/Genentech and UCB, Speakers bureau: AbbVie, Amgen, BMS, Corrona, Crescendo, Janssen, Pfizer, Roche/Genentech and UCB, C. Etzel Employee of: Corrona, LLC, C. Karki Employee of: Corrona, LLC, J. Ssemakula Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: Genentech, Inc, Consultant for: Genentech, Inc, Employee of: Corrona, LLC, A. Shewade Employee of: Genentech, Inc, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Novartis and Pfizer, Employee of: Corrona, LLC